A genome scan for loci influencing total serum immunoglobulin levels: possible linkage of IgA to the chromosome 13 atopy locus. - Wiltshire,S; Bhattacharyya,S; Faux,JA; Leaves,NI; Daniels,SE; Moffatt,MF; James,A; Musk,AW; Cookson,WO (Hum Mol Genet, 1998)
Immunoglobulins play an essential part in the immune system, and immunoglobulin deficiencies can have profound medical consequences. The genetic control and regulation of the immunoglobulin response is therefore of interest. Previous investigations have identified a number of loci influencing total and specific IgE levels. In this study, 80 nuclear families have been examined for linkage of total serum IgA, IgG and IgM levels to a genome-wide panel of microsatellite markers. Potential quantitative trait loci influencing IgA levels have been identified on chromosomes 10 and 13, and possible loci influencing IgG levels were found on chromosomes 3 and 13. No significant linkages to IgM levels were found. The linkage of IgA on chromosome 13 was to a marker previously linked to IgE responses (atopy). Linkage to IgG was in the same region but to a more distal marker. None of the factors known to influence immunoglobulin expression map to the loci identified in the present study. These loci are therefore likely to contain previously unrecognized components of the immunoregulatory system.